2019
DOI: 10.1038/s41467-019-12864-5
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating topological transformations of polar structures through real-time observation of the dynamic polarization evolution

Abstract: Topological structures based on controllable ferroelectric or ferromagnetic domain configurations offer the opportunity to develop microelectronic devices such as high-density memories. Despite the increasing experimental and theoretical insights into various domain structures (such as polar spirals, polar wave, polar vortex) over the past decade, manipulating the topological transformations of polar structures and comprehensively understanding its underlying mechanism remains lacking. By conducting an in-situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 60 publications
7
60
0
Order By: Relevance
“…3b–d shows distributions of strain components estimated from geometric phase analysis based on the STEM image. The white-colored sinusoidal wave-like out-of-plane strain pattern is observed within PTO layers along the [100] direction, suggesting the existence of long-range vortex ordering consistent with previous reports 21 , 22 , 31 . The dark field transmission electron microscopy (TEM) image shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…3b–d shows distributions of strain components estimated from geometric phase analysis based on the STEM image. The white-colored sinusoidal wave-like out-of-plane strain pattern is observed within PTO layers along the [100] direction, suggesting the existence of long-range vortex ordering consistent with previous reports 21 , 22 , 31 . The dark field transmission electron microscopy (TEM) image shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…As such, the vortex must be charged to the same extent as the H-H DW in Figure 2, with average = 1.09 e per PK-cell. Although the DW width is similar to the H-H case in Figure 2, the defined vortex polarisation suggests the charge density is concentrated at the vortex core [47], further increasing the relative conductivity difference versus the domain.…”
Section: Resultsmentioning
confidence: 72%
“…Damodaran et al (29) found phase coexistence of vortex and ferroelectric phases and electric-field-driven interconversion between them. Du et al (30) reported that vortices can split, transform to polar waves, and finally become a stable c domain that does not recover spontaneously. According to Chen et al (31), under mechanical stress, a polar vortex can be switched to an a domain and reversibly recover after removal of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Phase-field simulations have demonstrated the possibility of switching polar vortices: under the application of an electrical field, vortex cores with opposite curls move closer until they reach the same lateral position and then produce new a domains, and the reverse process of back-switching takes place when the applied field is removed ( 37 ). The evolution of vortices driven by temperature change ( 29 ), electric field, and stress have been probed experimentally by X-ray diffraction, PFM ( 29 ), and TEM ( 30 , 31 ). Damodaran et al ( 29 ) found phase coexistence of vortex and ferroelectric phases and electric-field-driven interconversion between them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation